Colloidal Clusters by Using Emulsions and Dumbbell‐Shaped Particles: Experiments and Simulations1. Issue 26 (10th May 2013) - Peng, Bo; Smallenburg, Frank; Imhof, Arnout; Dijkstra, Marjolein; van Blaaderen, Alfons
<x xml:space="preserve">Abstract</x> With (dumb)bells on: A variety of colloidal stereoisomers (all the same materials) have been prepared through evaporation of emulsions by using symmetric and asymmetric dumbbell‐shaped particles (see figure). The colloid configurations are in good agreement with the results of computer simulations.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>